“Analysing Impact of Work Environment on Employee Well-Being: To Flourish the Employee’s Performance in An Organisation” - Rupali P. Gawande, Sonali Jadhav, Sunita Kharate, Deepa Kedar Rele (European Economic Letters (EEL), 2024)
An organization's human capital is its most valuable asset since it consistently provides the intangible qualities of diligence, integrity, commitment, and efficiency that are never shown in the financial statement of the business. It is therefore the organization's primary responsibility to ensure that its workers have a healthy work environment. This assessment attempts to concentrate on the significance and connection between employee well-being and the work environment for the organization's progress. This study focuses on aspects of the workplace that lead to an increase in workers' well-being and may be positively correlated with both worker and organisational performance. For this research well-structured questionnaire is used data is collected from 60 employees working in organisations It has been noted that the office environment, employee interactions, help, and trustworthiness, as well as the significance of the employer and supervisor, all contribute to the well-being of employees. This research is expected to support more conventional methods of boosting employee perspectives and productivity, which can enhance organizational performance, effectiveness and productivity.